Analisis Konseling Individu dalam Mengatasi Trauma : Analisis Film Dear Zindagi - Lingga, Musdiansyah; Sriharini, Sriharini (CV. Ulil Albab Corp, 2024)
This research aims to analyze the concept of individual counseling applied in addressing trauma, using the film